Ecuadorian technological overview: patent applications in Ecuador between 2011 and 2020, review (Business Vision, 2021)
In the present, the literary review referring to the subject of patents, the presentation, approval statistics in Ecuador and the comparison with the countries at a global level is mentioned, in the study period between 2011 and 2020, the analyzed data not only Regarding patents, the topic of innovations is also covered, data provided by the World Intellectual Property Organization (WIPO), as study materials, data related to research and development spending in Ecuador are shown, as well as the origin of the applications, the evolution of patents presented in the decade of study, the data is also presented in which it relates the patents presented according to the technological area, in which Biotechnology is denoted as the most related to Technology followed by Chemistry of Materials and Medical Technology. As conclusions, a decreasing number of patents or innovations presented in the study decade is shown, but it mentions the FabLab Digital Manufacturing Laboratories as alternatives that could help the presentation of new projects, processes that could generate patents and innovations in the country.
Keywords: Patents; Innovations; FabLab